Role of societal norms in raw sewage disposal in water sources, Mukuru slums, Nairobi County, Kenya - Nasirumbi, Audrey; Patrick Kinyua Kubai; Dorothy Kithinji Kagendo (African Journal of Science, Technology and Social Sciences, 2025)
A sustainable sanitation system is economical, socially acceptable, and environmentally friendly. Raw sewage disposal into water sources is a significant environmental and health concern in many informal settlements in Kenya. Inadequate access to proper sanitation facilities leads to water source contamination. Despite the severe environmental and health impacts, there is limited knowledge about the factors influencing these practices. Therefore, this study`s specific objectives sought to determine the role of societal norms influencing the discharge of raw sewage into water sources in Mukuru slums, Nairobi, Kenya. A cluster proportionate random sampling was used to identify household heads, while key informants were purposively selected. A quantitative study of 246 household heads was conducted using structured questionnaires and analyzed using the Pearson Chi-Square Test at 95% Confidence Interval. Qualitative data collected through FGDs, and KIIs, was transcribed and manually presented in narratives. The study findings revealed that 96.1% of raw sewage was discharged into water sources while 87.7% of the participants witnessed raw sewage disposal practices. Raw sewage disposal had influenced societal norms such as belief that played a role in 85.1% of cases (p=0.046). The study concluded that poor societal norms contributed to raw sewage disposal into water sources. The study recommended community to educate her residents on values such as beliefs, collective responsibilities, the presence of social networks, proper communication, cooperation, and coordination to prevent raw sewage disposal in the area and create an enabling environment for all.